2007
DOI: 10.1002/14651858.cd004647.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ileostomy or colostomy for temporary decompression of colorectal anastomosis

Abstract: The best available evidence for decompression of colorectal anastomosis, either use of loop ileostomy or loop colostomy, could not be clarified from this review. So far, the results in terms of occurrence of postoperative stoma prolapse support the choice of loop ileostomy as a technique for fecal diversion for colorectal anastomosis, but large scale RCT's is needed to verify this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 35 publications
3
92
1
9
Order By: Relevance
“…In some systematic reviews, a loop ileostomy is not encouraged because of prolapse rates [11]. In other reviews, no clear preference is demonstrated [12].…”
Section: Discussionmentioning
confidence: 99%
“…In some systematic reviews, a loop ileostomy is not encouraged because of prolapse rates [11]. In other reviews, no clear preference is demonstrated [12].…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings besteht das Problem, dass dabei weder die parastomale Hernie noch der Stomaprolaps definiert wurden. Eine CochraneArbeit definiert die parastomale Hernie als eine Hernie neben dem Stoma und einen Stomaprolaps als eine Ausstülpung des Stomas durch die Bauchwand [13]. Unklar Die Follow-up-Untersuchung sollte ab dem 12.…”
Section: E Eine Bei Einer Klinischenunclassified
“…Peeters and colleagues 7 proposed that absence of a defunctioning stoma was a risk factor for symptomatic anastomotic leakage in patients undergoing total mesorectal excision for rectal cancer. A temporary loop ileostomy is preferred to colostomy by most surgeons because it is easy to construct and close without a risk of injury to the colic vascular arcade, and there are fewer problems with prolapse 8 .…”
Section: Introductionmentioning
confidence: 99%